The effects of UVB radiation on intumescence development and the characterization of lesions from physiological disorders on ornamental sweet potato (Ipomoea batatas), tomato (Solanum lycopersicum), and interspecific geranium (Pelargonium spp.) - Craver, Joshua Ken (Kansas State University, 2014)
Intumescences are a physiological disorder characterized by hypertrophy and possibly hyperplasia of plant cells. Many plant species are susceptible to intumescence development, but the specific causative factors remain uncertain. Ultimately, this disorder results in the death of the affected cells. Previous observations and research suggest that the quality and quantity of light to which plants are exposed may be a factor in development of the disorder. The purpose of the first study was to assess the preventive effect of UVB radiation on intumescence development in ornamental sweet potato (Ipomoea batatas). Two sweet potato cultivars, ‘Sidekick Black’ and ‘Ace of Spades,’ were grown under four light treatments of 1) Normal; 2) UVB; 3) UVB-Blocked; 4) Full-Spectrum. The ‘Ace of Spades’ cultivar was highly susceptible to intumescence development, while ‘Sidekick Black’ was much less susceptible to the disorder. For ‘Ace of Spades,’ the addition of UVB radiation significantly reduced the number of leaves affected with intumescences when compared to plants grown under the other light treatments. This study indicates a cultivar-specific effect of UVB light in minimizing intumescence development on ornamental sweet potato, therefore suggesting a potential genetic component in intumescence susceptibility. Many plant species are prone to similar physiological disorders in which lesions develop on the leaf tissue. Nomenclature for such lesions has varied significantly in the literature. Interchangeably using these terms causes confusion as to whether these names refer to the same or different disorders. The objective of the second study was to characterize the development of lesions on ornamental sweet potato (Ipomoea batatas ‘Blackie’), tomato (Solanum lycopersicum ‘Maxifort’) and interspecific geranium (Pelargonium ×‘Caliente Coral’). Light microscopy, field emission scanning electron microscopy (FESEM), and digital photography were used to observe lesion development on each species. Lesions on ornamental sweet potato predominately involved the hypertrophy of the palisade parenchyma through the upper epidermis, while geranium lesions involved the hypertrophy of spongy parenchyma cells restricted by the lower epidermis. Tomato lesions involved both the hypertrophy and hyperplasia of the lower epidermis and spongy parenchyma. Thus, different species possess varied cellular responses when developing lesions due to physiological causes.
Keywords: Controlled environment; Floriculture; Greenhouse production; Microscopy; Oedema; Ultra-violet light; Horticulture (0471); Plant Biology (0309); Plant Sciences (0479)